Development of an advanced nano-satellite (VELOX-I) - power management system - Seow, Weilun. (2012)
The objective of the project is to research and develop the power management system for an Advanced Nano-satellite built by Nanyang Technological University. The power management system has an on board 8051 micro-controller for control and communications. Having a micro-controller in satellite power system is not an uncommon practice and has been adopted in many past instances of power management systems design. This report contains in-depth introduction, implementation, discussion and testing done on all functions that are achieved with the use of the micro-controller. The end product of this project, which is the flight firmware for power management system, is solely developed by the author.